The Toxicity of Four Anticoagulant Rodenticides to Common Field Rat in the Laboratory - Alemayehu Woldeamanuel; Merid Kumsa; Million Teshome (Pest Managment Journal of Ethiopia, 2023)
The efficacy o f four anticoagulant rodenticides, viz. coumatetralyl, chlorophacinone + sulfaquinoxaline, bromadiolone and brodifacoum was evaluated under choice and no-choice regimes in the laboratory against the common field rat, Arvicanthis abyssinicus. In a no-choice test, brodifacoum was most toxic followed by bromadiolone, chlorophacinone + sulfaquinoxaline, and coumatetralyl. In all choice tests, poison consumption was significantly lower than the alternative plain bait. Acceptability test results among wheat-based anticoagulants revealed that bromadiolone was the most accepted poison while there was no difference among the rest of the chemicals. Except for bromadiolone and liquid coumatetralyl, the acceptance o f each test poison was below die USEPA acceptance threshold of 33%.